PENGARUH PROFITABILITAS, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN DAN KEPEMILIKAN MANAJERIAL TERHADAP STRUKTUR MODAL - Pattinasarani, Stefany Christianingsih; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Capital structure is a permanent expenditure which reflects the balance between long term debt and own capital. This research is meant to observe the influence of profitability, sales growth, firm size and managerial ownership to the capital structure on manufacturing companies which are listed in Indonesia stock exchange. The sample of this research is 142 manufacturing companies which are listed in Indonesia stock exchange (IDX) in 2011-2014 periods and 33 of 142 manufacturing companies which have met the sample criteria that consists of many sectors have been selected as saamples. The sample collection technique has been done by using purposive sampling. The result of partial test shows that profitability has significant and negative influence; firm size has significant and positive to the capital structure. Meanwhile, sales growth and managerial ownership do not have any influence to the capital structure.Keywords: profitability, sales growth, firm size, managerial ownership, capital structure.ABSTRAK